A Preliminary Embodiment Short Questionnaire - Eubanks, James Coleman; Moore, Alec G.; Fishwick, Paul A.; McMahan, Ryan P. (Frontiers in Virtual Reality, 2021)
Consumer virtual reality (VR) technologies have made embodying a virtual avatar during an immersive experience more feasible. The sense of embodiment towards that virtual avatar can be characterized and measured along three factors: self-location, agency, and body ownership. Some measures of embodiment have been previously proposed, but most have not been validated or do not measure the three individual factors of embodiment. In this paper, we present the construction and validation of a preliminary version of a short questionnaire that not only addresses these factors of embodiment but can also be used as an in-VR questionnaire, which we call the pESQ. By using and validating the pESQ, we provide results indicating that foot tracking significantly improves self-location and agency, and that an avatar significantly improves body ownership.